1987
DOI: 10.1346/ccmn.1987.0350303
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Vermiculite-Anilinium Intercalate

Abstract: Abstract--If anilinium ions are intercalated into Llano vermiculite, the stacking order of adjacent silicate layers is increased, resulting in a relatively sharp single crystal X-ray diffraction (XRD) pattern. The packing of intercalated organic members forms a superstructure and produces bonding from layer to layer which favors the stacking order. Superlattice reflections occur which, although sharp in the a'b* plane, are streaked along c*. Apparently there is little coherence between adjacent layers of order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Based on electron microprobe analyses, Slade et al (1987) give an interlayer charge for Na-saturated Llano vermiculite of 0.93 per [Ore(OH)2]. This is similar to the interlayer charge of Ontario phlogopite (0.94), whereas our Llano vermiculite has an interlayer charge of 0.88, as shown above.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Based on electron microprobe analyses, Slade et al (1987) give an interlayer charge for Na-saturated Llano vermiculite of 0.93 per [Ore(OH)2]. This is similar to the interlayer charge of Ontario phlogopite (0.94), whereas our Llano vermiculite has an interlayer charge of 0.88, as shown above.…”
Section: Resultssupporting
confidence: 72%
“…Thus, a perpendicular arrangement of alkyl chains in weathered mica may not be possible. Slade et al (1987) also reported that some interlayer sites in Llano vermiculite were still occupied by inorganic cations after intercalation of anilinium ions. However, energy-dispersive X-ray analysis of both phlogopite and K-depleted phlogopite (Ca-phlogopite) revealed that the remaining K was derived from nonexpanded K-layers in the alkylammonium-treated sample.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, the intercalation of alkylammonium ions in the interlayers of vermiculite appears to improve the degree of ordering of 2 : 1 layers in these minerals. Three dimensional X-ray patterns of Llano vermiculite intercalated with anilinium ions (Slade et al, 1987) confirm this observation.…”
Section: Discussionsupporting
confidence: 56%
“…A trial model for the silicate structure was derived from the atomic coordinates given by Slade et aL (1987).…”
Section: Structure Determination: Initial Adjustment O F Silicate-laymentioning
confidence: 99%
“…Alcover et al (1973) suggested that the exchangeable inorganic cations and water molecules in a Kenya vermiculite were also distributed over the lattice points in a C-face centered cell with dimensions 3a x b, which, by inference, represented t h e charge distribution in the silicate layers. For the Vermiculite from Llano County, Texas (LV), de la Calle et aL (1976), Thompson (1984), and Slade et aL (1987) showed that only short-range ordering of tetrahedral cations exists in local domains. Consequently, if local charge balance operates in LV, its interlayer cations should also be ordered only in local domains; however, for the Nyasaland and Kenya vermiculites, the local domains of short-range order may well be larger.…”
Section: Superstructurementioning
confidence: 99%